The effect of Turmeric Oil on The joints of white rats treated with aqueous extract of tobacco (Submission and Review of Research -Biological Sciences Series, 2025)
This study demonstrates the effect of Turmeric Oil on the damage caused by the aqueous extract of tobacco leaves in rheumatoid arthritis through measuring (rheumatoid factor RF, C-reactive protein CRP) in the blood of white rats. The study included 36 two-month old male albino rats of the Balb/c lineage, distributed into 6 groups (6 in each group). The first group was given only water and food, the second group was given turmeric oil at a dose of 500 mg/kg for a month to ensure its safety, while the third group was given 300 mg/kg of tobacco leaf aqueous extract for a month to evaluate the damage resulting fram the extract, and the fourth group was also given 300 mg/kg of the extract with 500 mg/kg turmeric oil simultaneously for a month to study the protective effect of the oil As for the fifth treatment group, it was given 300 mg/kg of the extract whole month, then it was given 500 mg/kg of turmeric oil for a month to evaluate the therapeutic effect of the oil by comparing it with the sixth group, which was given 300 mg/kg of the extract for a month, then it was treated with a non-steroidal anti-inflammatory drug (celex) at a dose of 30 mg/kg for a month, then blood samples were collected for analysis. The results were as follows: There were no significant differences (P>0.05) in the second group for both RF and CRP, whereas the dose with the aqueous extract of tobacco leaves led to a significant increase in both RF and CRP (p<0.05) in the third group compared to the first, while they decreased in the fourth preventive group and fifth therapeutic group (p<0.05), where the results were close to the sixth group.